PEMBERDAYAAN KADER POSYANDU LANSIA DALAM SKRINING DAN PENGOBATAN PENYAKIT HIPERTENSI DAN KENCING MANIS - I.N.G. Wardana; I.G.A. Widianti; I.N.M. Karmaya (Buletin Udayana Mengabdi, 2023)
In 2050, BPS projects that the number of elderly people will be 74 million, or about 25% of the population. In 2050, BPS projects that the number of elderly people will be 74 million, or about 25% of the population. The elderly are a vulnerable group to suffer from hypertension and diabetes. The advancement of current health technology makes it easier for someone to check their pressure and blood sugar to screen for these two diseases. By providing training to elderly cadres on how to measure blood pressure and blood sugar and their interpretation, it is hoped that they will be able to screen for these two diseases independently during posyandu activities. This service is carried out by providing training to the elderly Banjar Umadesa cadres on how to check blood pressure and blood sugar levels with a digital tensimeter and glucometer. After the cadres are trained, health service activities will be provided free of charge to the elderly. There were 50 elderly who attended this activity (29 men and 21 women). Hypertension was found in 15 people (30%) and diabetes in 2 people (4%). But apart from these two diseases, hyperuricemia was found in 12 people (24%), and hypercholesterolemia in 8 people (16%). Elderly cadres can independently measure the blood pressure and blood sugar of the elderly during Yankes activities. With the discovery of a high prevalence of hyperuricemia and hypercholesterolemia, in the future the elderly cadres of Umadesa Banjar need to be given training to measure uric acid and cholesterol levels. hypercholesterolemia, in the future, the elderly cadres of Banjar Umadesa need to be given training to measure uric acid and cholesterol levels. Keywords: elderly, elderly cadres, hypertension, diabetes, community service.